Sosialisasi dan Edukasi Zakat Produktif kepada Masyarakat di Kecamatan Jatinangor - Ahmad, Yono Ali; Supriatna, Yana Achmad; Sunarti, Teti (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This article aims to describe the process and impact of productive zakat socialization and education to the community in Jatinangor District. This activity is designed to improve the community's understanding of the concept of productive zakat and how to optimize it as a tool for economic empowerment. This research used a qualitative approach with descriptive method to explore the community's perception before and after the socialization. The results showed that socialization and education significantly improved community understanding and participation in the productive zakat program. In addition, economic empowerment through productive zakat is also proven to contribute to the improvement of community welfare